Prof: M S Pavgi Award Lecture - Pea-powdery mildew-an ideal pathosystem - SINGH, U.P. (Indian Phytopathology, 2002)
Recent research on the pea-powdery mildew (Erysiphe pisi) pathosystem is reviewed with particular reference to symptomatology, spore germination, development of the pathogen on susceptible and resistant pea cultivars, and control of powdery mildew by some novel chemicals, plant products and biological agents.